Cita Rasa dan Ekuitas Merek PENGARUH CITA RASA DAN EKUITAS MEREK TERHADAP MINAT BELI INDOMIE GORENG RASA RENDANG: (Studi Kasus pada Konsumen Indomie di Kecamatan Pancoran Mas, Kota Depok) - Oktavia Damayanti; Fortuna Zain; Nidia Sofa (Administratif Profesional, 2023)
This study aims to determine and analyze whether there is a partial and simultaneous influence between Taste and Brand Equity on consumer buying interest in Pancoran Mas District, Depok City. This study uses causal associative research with a quantitative approach. Data collection used in this study were primary and secondary data. The data analysis employed instrument test analysis, classical assumption test, and hypothesis testing. The sample was determined using a purposive sampling method and analyzed using SPSS version 25. The sampling formula used was the Slovin formula, and obtained a total sample of 100 respondents. The regression equation model in this study is Y = -14.934 + 0.753X1 + 0.607X2 + e that this study is feasible to use. The results of this study indicate that taste and brand equity simultaneously affect consumer buying interest in Indomie Goreng Rendang, with a large effect of 56.6%. Partially, the taste has a positive and significant effect on buying interest, and brand equity has a positive and partially significant effect on buying interest Key Word : Taste, Brand Equity, Buying Interest